1984
DOI: 10.1159/000233581
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Antibody-Dependent Cellular Cytotoxicity and Natural Cytotoxicity by Retinoic Acid

Abstract: The present study has shown that in vitro antibody-dependent cellular cytotoxicity and natural cytotoxicity of human blood lymphocytes are inhibited by retinoic acid (5·10-4M). The inhibition of cytotoxicity is due to a specific effect on the effector lymphocytes and not to an effect on the target cells. The reduction of killing is most pronounced with prolonged incubation (20 h) of the killer cells with retinoic acid, recovery of killer and natural killer cell activity occurring with post-treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…These results are in agreement with the report of McKerrow et al of depressed NK cell activity in acne patients treated with 1.0 mg/kg per day isotretinoin 17 . Two other groups have previously shown that treatment of lymphocytes with retinoic acid in vitro strongly inhibits NK activity, acting antagonistically to the immunostimulatory effects of IFN 18 , 19 . In contrast, Pigatto et al showed that patients with acne or psoriasis treated with etretinate 1.0 mg/kg per day had enhanced NK activity, while an isotretinoin‐treated group did not show any significant changes, both in vivo and in vitro 20 .…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the report of McKerrow et al of depressed NK cell activity in acne patients treated with 1.0 mg/kg per day isotretinoin 17 . Two other groups have previously shown that treatment of lymphocytes with retinoic acid in vitro strongly inhibits NK activity, acting antagonistically to the immunostimulatory effects of IFN 18 , 19 . In contrast, Pigatto et al showed that patients with acne or psoriasis treated with etretinate 1.0 mg/kg per day had enhanced NK activity, while an isotretinoin‐treated group did not show any significant changes, both in vivo and in vitro 20 .…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with those of Eremin et al (1984) who reported an inhibition of T lymphocyte rosettes with retinoic acid treatment. However, it is unclear whether the decrease of lymphocytes forming E-rosettes after incubation in vitro with retinoids and carotenes is actually due to decreased Figure 4 Effect of retinoids and carotenes on natural killer (NK) cell activity.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, it has been reported that NK activity, phagocytic and tumouricidal activities of macrophages are enhanced by incubation with retinoids in vitro(Goldfarb & Herberman,1981;Tachibana et al,1984). On the other hand,Eremin et al (1984) found that retinoic acid inhibited antibody-dependent cellular cytotoxicity and natural cytotoxicity of human blood lymphocytes. With the exception of the higher concentration (10~ M) of retinol and retinal, our studies showed no augmentation or reduction of NK activity after incubation in vitro with any concentrations of retinoids or carotenes.…”
mentioning
confidence: 99%
“…Previous in vitro studies of the effects of retinoids on NK cell activity and IFN production suggest that retinoids inhibit these functions (42)(43)(44)(45)(46). Although some of our XP patients (patients 1, 2, 3, 5, and 7) were being treated with isotretinoin at the time we assayed their NK cell activity, it is unlikely that our ex vivo study of lymphocytes from XP patients simply reflect the effects ofretinoids on NK cell function.…”
Section: Discussionmentioning
confidence: 92%